Therapeutic Body Wraps in Swiss public adult acute inpatient wards. A retrospective descriptive cohort study. Issue 3 (29th April 2016) - Opsommer, E.; Dubois, J.; Bangerter, G.; Panchaud, R.; Martin, D.; Skuza, K.
Accessible summary: What is known on the subject?: Various expert opinions reported relational benefits and tranquilizing effects of therapeutic body wraps (TBW) in adults experiencing high anxiety in the context of psychosis. Yet, this tranquilizing effect was never investigated in larger samples and in the context of modern psychopharmacology. What this paper adds to existing knowledge?: This is the first study to establish descriptive statistics of this mind‐body therapy in French‐speaking Switzerland where TBWs are routinely used in two public psychiatric hospitals. It brings knowledge on patients nowadays treated with TBW. Moreover, it opens a new area of investigation on the potential of this nursing technique, which may contribute to reduce anxiolytic medication in severely ill patients. What are the implications for practice?: This study sheds light on a clinical practice in mental health nursing and upon nurses' specific contribution to psychiatric clinic. It investigates a potential for TBWs to reduce the use of anxiolytic medications by patients who agreed to have TBW as part of their treatment. It may help to inform the mental health nursing practice. Abstract: Introduction: Many patients suffering from serious mental illness experience severe anxiety and those with psychosis often report the feeling of their bodies falling apart. While it is believed that these patients benefit from therapeutic body wraps (TBWs), the use of this adjunct therapy has rarely been studied in adult patients. Aims: The aim of this study was to obtain descriptive statistics on the clinical, social‐demographic and institutional reality of TBW therapy in Swiss public adult inpatient wards. Methods: Retrospective data related to a cohort of 172 adult inpatients were retrieved from records of two public hospitals. Correlations between TBW and the prescriptions of lorazepam were explored. Results: TBWs were primarily used for patients diagnosed with either schizophrenia, schizotypal, delusional and other non‐mood psychotic disorders or mood disorders. Patients had, on average, four psychiatric hospitalizations, and in 30% of the cases, TBWs were offered during the first hospitalization. Moreover, TBWs were mostly practiced by nurses. Body wraps were potentially associated with a reduction in both anxiolytic and neuroleptic drugs. Discussion/Implication for practice: Based on our results, TBW might contribute to the clinical management of anxiety by nurses. The efficacy of TWB regarding anxiety has yet to be investigated in a randomized controlled trial.